Measuring the impact of integration and diversification on firm value in the food industry - Dorsey, Sarah Gayle (Kansas State University, 2006)
The strategic decision a firm makes in determining where to set its vertical and horizontal boundaries is a widely discussed topic in the literature. This strategic decision can include vertical integration, horizontal integration and diversification outside of the food economy. These activities can impact a firm in different ways. The objective of this research is to determine whether food economy firms pursuing diversification or integration are valued lower or higher as a whole than the sum of their individual segments. This is commonly referred to as a premium or discount. The hypothesis is that a premium exists for food economy firms that pursue integration activities and a discount exists for food economy firms that pursue diversification activities. Four separate food economy sectors are used in the analysis: food processing, wholesale grocery, retail supermarkets, and restaurants. To determine whether a premium or discount exists for integration or diversification, an excess value calculation method is used which compares the actual value of a firm to the imputed value of all of the segments of a firm. This excess value is then used in a seemingly unrelated regression (SUR) framework to determine how certain firm characteristics influence firm value. But, these firm effects may both lead a firm to diversify or integrate and affect firm value. This would incorrectly attribute a premium or discount to the diversification or integration itself and not the underlying firm characteristics that caused the firm to pursue such a strategy. To account for these underlying firm and industry characteristics, Heckman’s two-stage procedure is used to control for the self-selection of firms that diversify. The SUR results indicate that the hypothesis that integration leads to a premium for food economy firms cannot be rejected for the restaurant sector and for the processing sector except in the case of vertical integration into retail. The endogeneity tests indicate that, in most cases, the diversification or integration decisions are endogenous meaning that the firm effects that cause firms to diversify or integrate are positively or negatively correlated with firm value. In the cases of vertical integration into wholesale in the processing and restaurant sectors and unrelated diversification in the restaurant sector, including a self selection parameter makes the premiums found using SUR become discounts.
Keywords: Food industry; Integration; Economics, Agricultural (0503)